Revealing a Forgotten Poet: The Persian Literary Contributions of Ghulam Ali Maddah in Sindh - Nazir, Muhammad (sourcecoder, 2024)
Over the past thousand years, Persian language and literature have spread across a vast region, from the shores of the Bay of Bengal to Eastern Europe, significantly influencing these areas. In India and Sindh, where Persian is not commonly spoken, many scientific and literary works have been produced in Persian, like Iran and Afghanistan, promoting the language. Numerous books and articles focus on Persian literary and scientific figures in this region, but most concentrate on India, with little attention given to Persian literature in Sindh. Many poetry collections, mystic stories, and love epics remain unknown in private or public libraries in Pakistan's Sindh province and other countries worldwide. The most talented poets and writers from this area are still unfamiliar to the Persian-speaking world. Ghulam Ali Madah was one such lesser-known figure in literature and science from Sindh. He lived during the Kalhora eras and was a notable poet who excelled in writing Persian poetry and prose. Madah left behind two volumes of literary works written exclusively in Persian. This paper is an in-depth analysis of the life of Ghulam Ali Madah, his literary works, and his poetry. It covers all the research and studies done on him, shedding light on his contributions to Persian literature and his status as a poet.